Ocean Interconnectedness: An interdisciplinary workshop to learn from the ocean, through multisensory activities and reflections on the role of emotions in science and law: Senses & Science, Love & Law - Panieri, Giuliana; Poto, Margherita Paola; Bertella, Giovanna; Bertolotto Bianc, Giuliano; Médici, Natalia; Murray, Emily Margaret; Pandeva, Rada; Vita, Laura (Septentrio Reports, 2023)
The overall aim of this report is to document the experience and knowledge gained during the interdisciplinary workshop coordinated by Giuliana Panieri and Margherita Paola Poto on Ocean Interconnectedness. This event, organized at UiT The Arctic University of Norway on the 19th and 20th of September 2023, served as a pivotal platform for the convergence of various project outcomes. It synergized the achievements of Akma2 Ocean Senses, which advances ocean literacy through multisensory toolkits, alongside the endeavours of ECO_CARE and Follow Your Heart, dedicated to fostering emotional and ecological education and research. This event marks the kick-off of The Ocean Incubator Network, a newly established network funded by UArctic. Moreover, this workshop welcomed insights and contributions from other projects and departments, including the School of Business and Economics at the UiT The Arctic University of Norway, The Deep Network Project, and The Thalassophile Project. Together, we aim to create a dynamic and comprehensive platform for the exchange of ideas, knowledge, and collaboration in the realm of ocean-related education and awareness.